Revitalisasi Seni Hadrah ISHARI - Al-Am, Maftah Rozani; Afan, Suhaimi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research explores the revitalization efforts of Hadrah ISHARI art in Kras, Kediri as a form of sustainable cultural education. In the context of rapid globalization, the art of Hadrah ISHARI is often marginalized. Therefore, this research aims to not only preserve Hadrah ISHARI, but also integrate it into the context of formal and non-formal education. Using a qualitative approach, this research analyzes how the revitalization of Hadrah ISHARI can be a medium to instill cultural, historical, and social values to the younger generation. Data collection techniques include observation, in-depth interviews, and documentation. Through interviews with educators and students, this research reveals the potential of Hadrah ISHARI as an effective learning tool. The results show that the revitalization of Hadrah ISHARI not only increases people's appreciation of traditional arts, but also contributes to character development, creativity and a sense of belonging to cultural heritage. The active participation of the community, especially the younger generation, in this revitalization process shows that Hadrah ISHARI can be a bridge between the past and the future, while strengthening local identity and social cohesion.